2006
DOI: 10.1080/02770900600566611
|View full text |Cite
|
Sign up to set email alerts
|

The C523Aβ2Adrenergic Receptor Polymorphism Associates with Markers of Asthma Severity in African Americans

Abstract: Our goal was to explore associations between ss2 adrenergic receptor polymorphisms and markers of asthma severity in African American and Caucasian patients with asthma. Polymorphisms at loci -1023, -654, -47, 46, 79, 491, and 523 were genotyped and haplotypes were imputed in 143 African Americans and 336 Caucasians. C523A genotype associated with percentage of African Americans (but not of Caucasians) having an asthma exacerbation: AA, AC, and CC genotypes were 17, 29, and 40%, respectively (p = 0.018). Sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 46 publications
4
21
1
Order By: Relevance
“…More than a dozen additional SNPs have been reported, but many of them are rare, and the available knowledge on their functional relevance is limited for all of them, particularly with regard to drug-response studies (Brodde, 2008). The genotypes Gly16 and Glu27 are frequent in whites (approximately 50%), but a somewhat different prevalence may exist in other ethnicities (Table 1) (Hawkins et al, 2006;Lima et al, 2006;Wu et al, 2006). Genotype-phenotype association studies for the frequent R16G and Q27E variants have largely remained inconclusive with regard to arterial hypertension and other cardiovascular diseases (Hahntow et al, 2006;Rosskopf et al, 2007).…”
Section: Pharmacogenomics Of Gpcr Ligands In Cardiovascular Medicinementioning
confidence: 99%
“…More than a dozen additional SNPs have been reported, but many of them are rare, and the available knowledge on their functional relevance is limited for all of them, particularly with regard to drug-response studies (Brodde, 2008). The genotypes Gly16 and Glu27 are frequent in whites (approximately 50%), but a somewhat different prevalence may exist in other ethnicities (Table 1) (Hawkins et al, 2006;Lima et al, 2006;Wu et al, 2006). Genotype-phenotype association studies for the frequent R16G and Q27E variants have largely remained inconclusive with regard to arterial hypertension and other cardiovascular diseases (Hahntow et al, 2006;Rosskopf et al, 2007).…”
Section: Pharmacogenomics Of Gpcr Ligands In Cardiovascular Medicinementioning
confidence: 99%
“…Haplotype associations were noted for the bronchoprotection, but not for the acute bronchodilator effect. Several other studies have shown associations with ␤ 2 AR 5Ј-flanking SNPs or haplotypes and agonist (or related) phenotypes (18)(19)(20). Of note, in these latter studies in particular, haplotypes were often "reduced" to encompass one or two individual SNPs in the coding region based on linkage disequilibrium and the limited number of patients with certain haplotypes.…”
Section: Table 2 Results Of Electrophoretic Mobility Shift Assay Stumentioning
confidence: 99%
“…The intronless ␤ 2 AR gene has at least 20 polymorphisms in the promoter, 5ЈUTR, and 5Ј-leader cistron (collectively termed here as the "5Ј-flanking region"), which have allele frequencies of 0.05 (5%) in U.S. individuals of European or African descent (11,14). Clinical studies (11,(15)(16)(17)(18)(19)(20) using haplotypes derived from various sets of 5Ј-flanking and coding single-nucleotide polymorphisms (SNPs) have revealed several, and sometimes discordant, findings (see Discussion). To begin to understand the basis for in vitro and clinical phenotypes, in the current study, we have examined each polymorphism within the context of the binding of transcription factors derived from both human airway smooth muscle and airway epithelial cells.…”
mentioning
confidence: 99%
“…Due to these results, it has been hypothesized that genetic polymorphisms in the β 2 -adrenergic receptor may have influenced the response to salmeterol because the frequency of polymorphisms in the β 2 -adrenergic receptor occur more frequently in African-Americans compared with the overall population 11,27,28 . However, the impact of these genetic polymorphisms on serious asthma outcomes is unclear, and existing data indicate that genotype may not affect the phenotypic response to salmeterol 22 .…”
Section: The Smart Studymentioning
confidence: 97%